Postoperative Admission of Adult Craniotomy Patients to Neuroscience Floor Unit Reduces Cost and Length of Stay. (1st September 2019) - Sun, Matthew Z; Babayan, Diana; Chen, Jia-Shu; Wang, Maxwell; Naik, Priyanka; Reitz, Kara; Kim, Won
Abstract: INTRODUCTION: The neurointensive care unit (NICU) is costly but has traditionally been the default recovery unit after adult elective craniotomies for brain tumor resection. Given the rising healthcare costs and associated change in practice patterns, we assessed whether admitting these patients to a neuroscience floor unit instead of NICU for recovery resulted in an equivalent outcome while reducing the cost and length of stay. METHODS: We retrospectively analyzed the clinical and cost data of all adult brain tumor elective supratentorial craniotomy patients at a university hospital within the last 5 yr who had a length of stay of less than 7 d. We compared those who stayed in the ICU for 1 d during admission versus those who did not stay in the ICU. Patients undergoing shunts, endoscopic, burr hole craniotomies, posterior fossa craniotomies, and vascular procedures were excluded. RESULTS: A total of 688 patients were included, with 428 patients staying in the NICU for 1 d (NICU1) and 259 not staying in the NICU (NICU0). There was no difference in University Hospital Consortium (UHC) expected length of stay ( P = .338). However, the actual length of stay for the NICU1 group was 12 h longer than the NICU0 group (3.6 vs 3.1 d) ( P < .0001), and the difference was still significant in multivariate analysis controlling for age, MS DRG, OR hours, insurance type, discharge disposition, and admit day. While the NICU1 group had longer surgeries (mean OR hours charged 6.8 vs 6.5 h), there was no statistically significant difference in the cost of surgery. The NICU0 group reduced the direct hospital cost by 3070 per admission on average ( P < .001). Clinically, there were no statistically significant differences in the rate of return to OR, ED readmission, or hospital readmission within 30 d. CONCLUSION: Admitting to a neuroscience floor unit reduced the length of stay and direct hospital cost associated with admission, without significant differences in clinical outcome.